Rainfall analysis in consideration of climate change - Goh, Janelle Pei Fen (2019)
In recent decades, Singapore has experienced an increase in extreme rainfall events. Researches attribute part of this increase to climate change. Hence, this report studies the impact of climate change on the future rainfall pattern in Singapore. With current rainfall pattern, future rainfall patterns for Singapore were obtained through a weather downscaling simulator, LARS-WG, and updated Intensity-Duration-Frequency (IDF) curves were developed through Gumbel’s Extreme Distribution. Through analysis of the rainfall patterns over three different time periods; 2021 – 2040, 2041 – 2060, 2061 – 2080, it was conclusive that the mean rainfall will increase over the century, with minimal changes to the climate pattern in Singapore. It is expected that the end century, 2061 – 2080, would have higher rainfall as compared to that of earlier century, 2021 – 2040. Despite the increase in mean rainfall, the frequency of rainfall will remain relatively constant. Looking at future extreme rainfall events, hourly rainfall intensity is projected to increase between 5.88% to 13.78% between the period 2021 to 2080.